Penggunaan google classroom sebagai media pembelajaran daring mata pelajaran PKn di kelas V sekolah dasar - Novika Harumi; Hasan Mahfud; Roy Ardiansyah (Didaktika Dwija Indria, 2022)
Online learning in the pandemic is obstacle for both side of educational services user. Google Classroom learning media is one of the learning media that can support teaching and learning so that students can still attend school despite distance constraints. The purpose of this study is to describe the use Google Classroom and the obstacle faced in the learning process with Google Classroom as learning media. The research method used is the qualitative method with a phenomenological approach. This research was conducted at SDN Purwotomo No. 97 with a sample of 7 people. The instruments used are interviews, observations, and documentation. Based on the results of the study, the use of Google Classroom as a learning medium is considered effective by utilizing the features contained in Google Classroom and according to the circumstances of teachers and students. Common obstaacles are unstable signal networks and loss of students focus due pop-up notifications that appear during learning.